Laptops for students: strength and weakness of the portuguese initiatives - Carvalho, Ana Amélia Amorim (2011)
This paper focuses on the Portuguese initiatives to offer laptops with Internet connection to students at a reduced price. Five initiative were launched: "Schools, teachers and laptops" (2005 - 2006), "e-school" (e-escola) (2007 - 2008), "e-little school" (e-escolinha) with Magellan (2008 - 2009), "Learning and Innovating with ICT" (2010 - 2013), and this year "e-school 2.0" (e-escola 2.0). These initiatives are briefly described and criticized with regards to its strengths and weaknesses as well as teachers' ICT competencies to intregate laptops in the classroom